Impaired Social Behavior in 5-HT3A Receptor Knockout Mice - Smit-Rigter, Laura A.; Wadman, Wytse J.; Van Hooft, Johannes A. (Frontiers in Behavioral Neuroscience, 2010)
The 5-HT3 receptor is a ligand-gated ion channel expressed on interneurons throughout the brain. So far, analysis of the 5-HT3A knockout mouse revealed changes in nociceptive processing and a reduction in anxiety related behavior. Recently, it was shown that the 5-HT3 receptor is also expressed on Cajal-Retzius cells which play a key role in cortical development and that knockout mice lacking this receptor showed aberrant growth of the dendritic tree of cortical layer II/III pyramidal neurons. Other mouse models in which serotonergic signaling was disrupted during development showed similar morphological changes in the cortex, and in addition, also deficits in social behavior. Here, we subjected male and female 5-HT3A knockout mice and their non-transgenic littermates to several tests of social behavior. We found that 5-HT3A knockout mice display impaired social communication in the social transmission of food preference task. Interestingly, we showed that in the social interaction test only female 5-HT3A knockout mice spent less time in reciprocal social interaction starting after 5 minutes of testing. Moreover, we observed differences in preference for social novelty for male and female 5-HT3A knockout mice during the social approach test. However, no changes in olfaction, exploratory activity and anxiety were detected. These results indicate that the 5-HT3A knockout mouse displays impaired social behavior with specific changes in males and females, reminiscent to other mouse models in which serotonergic signaling is disturbed in the developing brain.